Use the chain rule to differentiate y=1/x^2-2x-1

First we will rewrite y so it is written with a power: y=1/x2-2x-1=(x2-2x-1)-1 Now let u=x2-2x-1 => du/dx = 2x -2 Writing y in terms of u: y=u-1 => dy/du= -u-2 = - 1/u2 using the chain rule: dy/dx = dy/du x du/dx =-1/ux (2x-2) substituting back in the value of u: =-(2x-2)/(x2-2x-1)= dy/dx

Answered by Alicia P. Maths tutor

16145 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Take the polynomial p(x)=x^4+x^3+2x^2+4x-8, use the factor theorem to write p(x) as two linear factors and an irreducible quadratic. An irreducible quadratic is a quadratic that can not be factorised.


How do you find stationary points of an equation, eg. y=x^2+3x+2


How do I do this question: A small stone is projected vertically upwards from the point A with speed 11.2 m/s. Find the maximum height above A reached by the stone.


How would I find the indefinite integral of x*cos(x) dx


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences